2014
DOI: 10.1002/ijc.29052
|View full text |Cite
|
Sign up to set email alerts
|

Elevated p53 promotes the processing of miR‐18a to decrease estrogen receptor‐α in female hepatocellular carcinoma

Abstract: The estrogen pathway has long been implicated as a tumor protector in female hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Our previous study identified that estrogen receptor alpha (ERa) protein is downregulated in 60% of female HCC cases, via a miR-18a elevation mediated suppression of ERa translation. This study aims to delineate the mechanism underlying the upregulation of miR-18a in female HCC. The analysis of 77 female HCC specimens revealed that miR-18a levels were associated with pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
0
32
2
Order By: Relevance
“…MiR-18a has shown different expression levels in different tumors. Previous studies have reported that miR-18a was highly expressed and exerted an oncogenic role across a wide spectrum of human solid cancers [25][26][27]. However, miR-18a expression was not changed compared with that of control K562 cells for reasons yet to be clarified, despite other members of the miR-17-92 cluster being upregulated in lentivirally transduced K562 clones [28].…”
Section: Discussioncontrasting
confidence: 51%
“…MiR-18a has shown different expression levels in different tumors. Previous studies have reported that miR-18a was highly expressed and exerted an oncogenic role across a wide spectrum of human solid cancers [25][26][27]. However, miR-18a expression was not changed compared with that of control K562 cells for reasons yet to be clarified, despite other members of the miR-17-92 cluster being upregulated in lentivirally transduced K562 clones [28].…”
Section: Discussioncontrasting
confidence: 51%
“…It is of great interest that miR-130a expression level was high in most female HCC patients. Till now, few miRNAs have been found to be correlated with sex [32,33]. Before the detailed function of miR-130a in female HCC patients is studied, the expression results are still needed to be confirmed in more female patients.…”
Section: Discussionmentioning
confidence: 94%
“…miR-18a belongs to the miR17-92 gene cluster, of which HIF-1α is a target gene (16). It has been reported that miR-18a serves a crucial function in the occurrence and development of myocardial ischemia (17), colonic neoplasm (18), liver tumors (19), prostate cancer (20) and malignant gliomas (21). Furthermore, a previous study suggests that miR-18a may be a specific biomarker for the early diagnosis and treatment of tumors (22).…”
Section: Discussionmentioning
confidence: 99%